2022
DOI: 10.22336/rjo.2022.42
|View full text |Cite
|
Sign up to set email alerts
|

The role of vitamin D in the onset and progression of diabetic retinopathy

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Vitamin D has properties such as lowering blood glucose, antioxidation, anti-inflammation, antiangiogenesis, and neuroprotection [124][125][126][127].A compelling correlation between serum vitamin D levels and the occurrence or seriousness of DR [128][129][130][131][132][133][134][135][136]. A prospective study found that maintaining adequate optimal levels of vitamin D in the bloodstream can prevent the deleterious impact of diabetes on the intricately interconnected microvasculature, including DR [137].…”
Section: Vitamin Dmentioning
confidence: 99%
“…Vitamin D has properties such as lowering blood glucose, antioxidation, anti-inflammation, antiangiogenesis, and neuroprotection [124][125][126][127].A compelling correlation between serum vitamin D levels and the occurrence or seriousness of DR [128][129][130][131][132][133][134][135][136]. A prospective study found that maintaining adequate optimal levels of vitamin D in the bloodstream can prevent the deleterious impact of diabetes on the intricately interconnected microvasculature, including DR [137].…”
Section: Vitamin Dmentioning
confidence: 99%
“…Vitamin D has properties such as lowering blood glucose, antioxidation, anti-inflammation, antiangiogenesis and neuroprotection [133][134][135][136]. There is a compelling correlation between serum vitamin D levels and the occurrence or seriousness of DR [137][138][139][140][141][142][143][144][145].…”
Section: Vitamin Dmentioning
confidence: 99%